In Ovo evaluation of antiviral effects of aqueous garlic (Allium sativum) extract against a velogenic strain of Newcastle disease virus - Fatemeh Doostmohammadian; Tahoora Shomali; Najmeh Mosleh; Mitra Mohammadi (Shahrekord University of Medical Sciences, 2020)
Introduction: The antiviral property of aqueous garlic extract against a virulent velogenic field isolate of Newcastle disease virus (NDV) was investigated in a time of addition assay in embryonated chicken eggs (ECEs). Methods: The ECEs were inoculated with the lowest concentration of the virus with HA (haemagglutination) positive activity. After determination of extract toxicity in ECEs, administration of different concentrations of the extract (0.5, 1, 2, 4 mg/mL) or ribavirin (comparative control) was performed 8 hours before (pretreatment), simultaneously (cotreatment) or 8 hours after (post treatment) virus injection. Allantoic fluids were harvested for infectivity determination, transmission electron microscopy (TEM) and viral load (HA titer) assay. In vitro HA blocking activity test was also performed. Results: Allicin content of the extract was 16.6% by HPLC method. The best viability results were related to the extract in pretreatment and ribavirin in co-treatment trials (p<0.05 as compared to infected ECEs with no treatment). Pre and co-treatment assays showed better results on HA titer of garlic treated groups. In infectivity assay, the 50% embryo lethal dose (ELD50) values of NDV were roughly 500 and 50 folds of ELD50 of the untreated virus in pre and co-treatment, respectively. No change was observed in viral shapes in TEM analysis nor HA blocking activity in vitro. Conclusion: Aqueous extract of garlic shows antiviral effects against a velogenic strain of NDV in ovo accompanied by a reduction in virus infectivity and titer. These effects are most pronounced in pretreatment trial.